Teachers' Understanding of Quality Reading Books in Brebes District Elementary Schools - Sandra Asri Annisa; Moh. Farizqo Irvan (FKIP - Universitas Riau, 2026)
Literacy plays a crucial role in enhancing students’ ability to comprehend information and develop critical thinking skills. Therefore, strengthening the literacy culture in schools requires the provision of quality reading materials that meet students’ needs and are appropriately selected by teachers. This study aims to analyze the level of elementary school teachers’ understanding of quality reading books in Brebes District and to examine differences based on gender and teaching experience. A descriptive quantitative approach was employed using a survey method involving 100 teachers selected through cluster sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics, including score calculation and percentage distribution for each indicator. The findings indicate that most teachers demonstrate a good level of understanding of quality reading books. Female teachers show slightly higher levels of understanding compared to male teachers, while teachers with shorter teaching experience tend to have slightly better understanding than those with longer experience. It is recommended that future research expand the study area and include additional variables related to literacy practices to provide a more comprehensive understanding of teachers’ competencies in selecting quality reading materials.